Developing Legal Framework for E-Court in Judicial Delivery - Aiqa Mohamad Zain, Nurul; Satirah Wan Mohamad Saman, Wan; Farik Mat Yatin, Saiful; Rahman Ahmad, Abdul; Saifuddin, Norshila; Nor Haliza Wan Mokhtar, Wan; Nurul Emyliana Nik Ramlee, Nik (International Journal of Engineering and Technology, 2018)
E-Court function is to manage electronic records in court. E-Court is expected to give such a lot of help for effective judicial delivery in Malaysia. Thus, by this research the implementation of e-Court is going to be explored in order to improve the system at all courts in Malaysia. This research applied qualitative case study methodology and data collection will be conducted at three units of high courts and will interview the stakeholders of the e-Court system. This is a conceptual paper to explore the implementation of e-Court system in Malaysian Judiciary, investigate judicial delivery issues in Malaysia and to propose a legal framework for e-Court in Malaysian civil courts. The study reviews literature on e-Court system and surveys from Malaysia and others countries. Studies related to this topic were analyzed and discussed throughout the paper in the context of implementation process, the judicial delivery issues and the future legal framework to be proposed.Â